Pekanbaru Street Art Park Dengan Pendekatan Arsitektur Ekspresionis - Awliya Rahmat Erviyus; Pedia Aldy; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A form of art that is growing in this modern era is seni jalanan or street art. The word "Street” in street art does not only show the location but rather shows the freedom of expression. Freedom of expression in general public became a push to the younger generation to roar and vent the angst over social, cultural, economic structure or whatever they feel by combining components of colours, lines, patterns and shapes in the city’s public spaces that have been overrun by advertising medias, billboards, banners, and etcetera. The usage of public spaces without permission to create street art is classified as a form of vandalism that could stains, damages, and spoils the city scape. However, the majority of society views street art as a form of art that leaves the impression of aesthetics in the midst of a hectic city life. Due to a minimal amount of the expression areas and the lack of attention from the government that even opposes the existence of this art form and assumes that this form of art as an act of vandalism. Expressionism architecture design approach that is also happen to be a refined result of imagination and emotions poured into an object to evoke emotions and understanding, certainly has a close relationship with the street art that acts as a media outlet of imagination and emotions poured into lines and shapes. The method of research that is used, covers observations, documentations as well as secondary data in a form of case studies and comparison studies. The concept applied to the design object is “Not everything’s the same” which is then influenced by a form of a graffiti’s writing style called Wildstyle and this concept also becomes a connecting point of each function’s placement. The outcome of this research is to design an architectural object that could evoke feelings and imaginations as well as conveys a message that is wished by the designers to the society through the principles of expressionism architecture.Keywords: Architecture, Expressionism, Street art.